Durable-Good Monopoly and Best-Price Provisions - Butz, David A. (American Economic Review, 1990)
Best-price provisions guarantee buyers that the prices they pay are the lowest available. If the seller subsequently cuts price, then each previous buyer is entitled to a refund. A durable-good monopolist who offers certain forms of these provisions can construct a consistent plan yielding the same profits as rental agreements and contracts with explicit quantity commitments. The provisions require special circumstances to be practical, but they are simple and effective and appear in a variety of economic settings. Three applications are discussed: international commodity agreements, markets for electric turbogenerators, and markets for financial claims.